1995
DOI: 10.1007/bf00329082
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation of ruminants to browse and grass diets: are anatomical-based browser-grazer interpretations valid?

Abstract: As a result of pioneering work of Hofmann (1973, 1989), nutritional ecologists classify ruminants into three feeding-type categories: browsers ("concentrate" feeders), grazers, and intermediate or mixed feeders. Hofmann proposed that these feeding types result from evolutionary adaptations in the anatomy of the digestive system and that one consequence is shorter retention of the digesta in the rumen of browsers, and thus a decreased efficiency of fiber digestion relative to that of grazers. We examined the hy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
121
7
3

Year Published

1996
1996
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(138 citation statements)
references
References 32 publications
7
121
7
3
Order By: Relevance
“…There have been two previous measurements of their mass by Robbins et al (1995) and Hofmann et al, (2008). Robbins et al provided no details of their mass.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There have been two previous measurements of their mass by Robbins et al (1995) and Hofmann et al, (2008). Robbins et al provided no details of their mass.…”
Section: Discussionmentioning
confidence: 99%
“…The size of the glands in giraffes (and okapi), which is relatively far smaller than in any other ruminant, clearly has a genetic component and perhaps an epigenetic one as it may be affected by the consistency of the diet with diets providing mechanical stimulation leading to hypertrophy (Kay, 1987), by the volume of saliva produced (Hofmann, 1989), by the amount of tannin neutralizing proteins secreted (Robbins et al, 1995), and /or variation in habitat, variation with seasons, increasing in summer and regressing in winter, and dissection technique . Hofmann et al also suggested that the small parotid gland in okapi and giraffes could be complemented by comparatively large mandibular, buccal and sublingual glands.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Robbins et al (1995) postulated that RR liquid flow rate in ruminants was independent of feeding type, and was RR liquid flow rate (ml h -1 ) = 11.5 BM 0.98 .…”
Section: Discussionmentioning
confidence: 99%